ANALISIS VEGETASI Ficus Racemosa L. DI BANTARAN SUNGAI CILIWUNG WILAYAH PANGADEGAN JAKARTA SELATAN: Analysis Vegetation Of Ficus Racemosa L In The Ciliwung District Of Pangadegan South Jakarta - Zaharah, Puteri; Noriko, Nita; Pambudi, Arief (Bioma, 2016)
River is the most important things for the human life, one of the components environmental especially for whom whose living in the city and Ciliwung river is one of the major river beside of others 13 rivers. Bamboo trees, bananas, cotton, gempol and elo are the common flora were dominate plants along the riverbanks (gempol and elo taken from the local people words). Based from interview with some local citizens in the Ciliwung riverbank which pas through the district of Pangadegan (South Jakarta), Ficus racemosa L (elo tree) is the most important plant which can withstand river erosion and could maintained the riverbanks during flood and continued by taking sample that plant on that district for need of analysis and identification. From the calculation Gigantochloa apus types stake has the highest INP value to the over all plot of 65.43% while INP Ficus racemosa is still low, but Ficus racemosa can be one alternative plant for conservation in the Ciliwung river, because Ficus racemosa has strong roots. However the selection of other plants such as bamboo trees is more effective because it has fast growth. Therefore, by combining the types of plants that role as conservation may be a solution.